Effects of folk medicinal plant extract Ankaferd Blood Stopper® on early bone healing - Sabri Cemil İşler; Sabit Demircan; Sırmahan Çakarer; Zerrin Çebi; Cengizhan Keskin; Merva Soluk; Emir Yüzbaşıoğlu (University of São Paulo, 2010)
OBJECTIVE: Several haemostatic agents are available for clinical use. Ankaferd Blood Stopper® (ABS), a mixture of five medicinal plant extracts, has been used historically as a haemostatic agent. The aim of this in vivo study was to investigate the effects of ABS on early bone healing using a rat tibia defect model. MATERIAL AND METHODS: Sixteen male Wistar rats were randomized into two groups of 8 animals each. After deep anesthesia with ketamine, bone defects (3 mm diameter and 2 mm deep) were created in the right and left tibiae of all animals and either treated with 1 cc of ABS (Group 1) or left untreated (Group 2; control). Surgical areas were closed primarily. The animals were sacrificed on the 7th postoperative day and bone samples were collected from the tibias. The samples were examined histopathologically for infection, necrosis, fibrosis, new bone formation and foreign body reaction. The histomorphometric results were analyzed statistically by the chi square test, with the level of significance set at p<0.05. RESULTS: Significant differences were found in both groups in terms of inflammation, necrosis and new bone formation (p=0.001, p=0.0001, p=0.001). No foreign body reaction was observed in the experimental group. ABS application decreased fibrosis in the experimental group, but there were no statistically significant differences from the control group. CONCLUSIONS: Histopathologically, it was observed that the application of ABS decreased the occurrence of inflammation and necrosis, while increasing new bone formation in early bone healing period. Further in vitro and in vivo studies are necessary for evaluating the benefits and possible adverse effects of the application of this herbal product on wound healing.